2012
DOI: 10.1128/aem.02190-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Quantification of Vibrio cholerae and Vibrio mimicus Cells in Water Samples by Use of Catalyzed Reporter Deposition Fluorescence In Situ Hybridization Combined with Solid-Phase Cytometry

Abstract: A new protocol for rapid, specific, and sensitive cell-based quantification of Vibrio cholerae/Vibrio mimicus in water samples was developed. The protocol is based on catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH) in combination with solid-phase cytometry. For pure cultures, we were able to quantify down to 6 V. cholerae cells on one membrane with a relative precision of 39% and down to 12 cells with a relative precision of 17% after hybridization with the horseradish peroxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Previous studies have found environmental water that contains 10 1 -10 4 CFU/mL V. cholerae cells. 18 Therefore, we decided to evaluate the efficacy of chlorine in deactivating V. cholerae one log higher at 10 5 CFU/mL. Each flask containing 500 mL water with different chlorine concentration was inoculated with 1 mL bacterial stock (10 7 CFU), which generated a 10 5 CFU/mL concentration of V. cholerae O1 (containers 1-11) or O139 (containers 12-22) in each flask.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found environmental water that contains 10 1 -10 4 CFU/mL V. cholerae cells. 18 Therefore, we decided to evaluate the efficacy of chlorine in deactivating V. cholerae one log higher at 10 5 CFU/mL. Each flask containing 500 mL water with different chlorine concentration was inoculated with 1 mL bacterial stock (10 7 CFU), which generated a 10 5 CFU/mL concentration of V. cholerae O1 (containers 1-11) or O139 (containers 12-22) in each flask.…”
Section: Methodsmentioning
confidence: 99%
“…Known numbers of V. cholerae O395 (source and growth conditions are listed in Table S1 in the supplemental material) were seeded into environmental water samples collected from a drinking water distribution system, the River Danube, and the Neusiedler See (an Austrian lake). The samples had been collected with sterile 2-liter glass bottles and transported to the laboratory at the in situ temperature (Ϯ2°C) in a cooling box within 3 h. The exact numbers of the added V. cholerae cell suspensions, prepared in 10% (final concentration) ethanol, were determined via epifluorescence microscopy and solidphase cytometry (SPC) as described elsewhere (9). Aliquots (2 ml; cell numbers of 5.4 ϫ 10 6 ml Ϫ1 ) were stored at Ϫ80°C to act as the standard for cell recovery estimations.…”
Section: Development Of the Qpcr Assay (I)mentioning
confidence: 99%
“…Permanent autochthonous occurrence of non-O1/non-O139 V. cholerae strains had been reported in these lakes, which are known for their high turbidity and high concentrations of DOC and humic substances (25,26). For solid-phase cytometry, 3 to 8 replicate subsamples of the appropriate volume (between 10 and 100 l, depending on the turbidity of the water) were taken and filled up with 1ϫ phosphatebuffered saline (PBS) to reach a final volume of 1 ml and processed as described by Schauer et al (9). Cultivation-based quantification of V. cholerae was done by membrane filtration as described by Schauer et al (9).…”
Section: Development Of the Qpcr Assay (I)mentioning
confidence: 99%
See 2 more Smart Citations